LGBT people and suicidality in youth: A qualitative study of perceptions of risk and protective circumstances. (September 2018) - Rivers, Ian; Gonzalez, Cesar; Nodin, Nuno; Peel, Elizabeth; Tyler, Allan
Abstract: Evidence suggests that lesbian, gay, bisexual and trans (LGBT) people are more likely to attempt to take their own lives in their youth when compared to heterosexual and/or cisgender people. This study draws on in-depth interviews with 17 LGBT individuals living in England, and explores the narratives used by participants to better understand their perceptions of risk and protective circumstances to explain suicide attempts in youth. Using a Goffman-informed thematic analysis, results identified three key themes that were linked to attempts to end life in youth. The first theme considers the conflicts resulting from first disclosure of sexual orientation and/or gender identity/trans status and being 'out' to others. The second theme explores participants' accounts of their concurrent mental health issues and how diagnoses of the mental health issues helped them make sense of their own experiences of attempted suicide. The final theme explores the experience of grieving over lost relationships and how that grief is received by others, including health professionals. Our results indicate that some LGBT individuals have effectively, although often arduously, navigated suicidal crises by utilising various approaches to coping. We provide a rich and layered picture of LGBT suicide risk in youth and potential resilience scenarios, although these are a reflection of our specific group of participants' experiences and realities. We argue that it is important to understand how LGBT individuals with a history of suicide attempts narrate and make sense of their experiences in early life and we suggest that the early negative experiences continue to have an effect on LGBT adults today. Highlights: LGBTs discuss perceptions of risk and protective circumstances in youth suicidality. Uses Goffman-informed analyses to identify themes linked to youth suicide attempts. Stories of conflict and coming out, mental illness concurrence and grief are told. Connectedness to other LGBT people and organisations supports well-being. Seeing LGBT suicidality scenarios as stages with plots, settings and people helpful.